A Study of Marketing Strategies of Software Firm: A Case of Syber Systems and Solutions - Singh, Surabhi (Journal of Research in Marketing (ISSN: 2292-9355), 2013)
Marketing of software firm consists of creating value, delivering value and communicating value to customers. This requires constant analysis of customer needs and technology up gradation. Marketing of software products is different from the traditional product due to uniqueness inherent in the product. (Nigam, 2011). The paper identifies the marketing challenges faced by the small software firms during the growth process. It starts with the study of small software firm and the influence of marketing strategies on the growth of same. Marketing strategy is more important for software companies now than it has ever been. The strategy of a software firm truly determines the phases it will undergo. The computer software industry is undergoing some major changes which are making an impact on software vendor business models, as well as marketing and sales tactics. A successful marketing strategy can change the present and future of any software firm. In such a competitive scenario where every software company is competing with each other, strong strategy enables them to have a competitive advantage over others. This case illustrates the determining factors of the successful marketing strategy for the software firm and its impact on the future of the firm.